The implications of sample preparation on the particle size distribution of soil. Issue 2 (4th February 2019) - Vdović, Neda; Pikelj, Kristina; Jurina, Irena; Ivanić, Maja; Dunato, Nadia; Štefan, Antonija
Abstract: Particle size distribution (PSD) is among basic parameters in soil and sediment characterization and provides essential information in sedimentological and environmental studies. The problem with the PSD determination is that for any given sample the result depends not only on the method used but also on the sample pre‐treatment, making them seldom comparable. In this study, the PSD of seven non‐treated and pre‐treated soil samples were determined by four granulometric methods (pipette, sedigraph, particle counter and laser diffraction analysis). Samples were subjected to pre‐treatments commonly used in sample preparation for the PSD determination, i.e ., addition of dispersant (sodium metaphosphate) and removal of the organic matter (with hydrogen peroxide). The total organic carbon (TOC) analysis was used to estimate the content of organic matter before and after its removal. The effect of different pre‐treatments was evaluated based on the PSD variations and the changes in the specific surface area (SSA) of the samples. The results highlighted differences in the PSD curves of samples depending on the granulometric method and pre‐treatment applied. The most pronounced difference was the higher amount of clay fraction determined by settling techniques. The role of hydrogen peroxide in disruption of aggregates was evident in the increase in the SSA as well as the share of fine fraction determined by all four techniques, while sodium metaphosphate made no modifications of the SSA but acted in favour of prolonging settling of clay particles and increasing its content obtained by settling techniques.